2020
DOI: 10.1002/eji.201948455
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo blockade of PI3K gamma or delta signaling enhances the antitumor potency of adoptively transferred CD8+ T cells

Abstract: Adoptive T cell transfer therapy induces objective responses in patients with advanced malignancies. Despite these results, some individuals do not respond due to the generation of terminally differentiated T cells during the expansion protocol. As the gamma and delta catalytic subunits in the PI3K pathway are abundant in leukocytes and involved in cell activation, we posited that blocking both subunits ex vivo with the inhibitor IPI‐145 would prevent their differentiation, thereby increasing antitumor activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 55 publications
3
42
0
Order By: Relevance
“… 92 The PI3K inhibitors described in this review decrease multiple inflammatory cytokines, including IL-1, TNF-α, IL-10, and IFN-γ. 43 , 93 However, idelalisib reduces cytokine production in macrophages, whereas duvelisib polarizes them to an M1 phenotype, leading to a more proinflammatory state. 22 , 50 , 55 Idelalisib and umbralisib reduce exhaustion marker expression on CD8 + T cells, which may assist in preventing lymphocyte dysfunction and depletion.…”
Section: Immunomodulation In Relation To Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“… 92 The PI3K inhibitors described in this review decrease multiple inflammatory cytokines, including IL-1, TNF-α, IL-10, and IFN-γ. 43 , 93 However, idelalisib reduces cytokine production in macrophages, whereas duvelisib polarizes them to an M1 phenotype, leading to a more proinflammatory state. 22 , 50 , 55 Idelalisib and umbralisib reduce exhaustion marker expression on CD8 + T cells, which may assist in preventing lymphocyte dysfunction and depletion.…”
Section: Immunomodulation In Relation To Sars-cov-2mentioning
confidence: 99%
“… 22 , 50 , 55 Idelalisib and umbralisib reduce exhaustion marker expression on CD8 + T cells, which may assist in preventing lymphocyte dysfunction and depletion. 93 Therefore, PI3K inhibitors could be useful in innate response modulation by inhibiting viral replication, improving early macrophage activation, and ameliorating the T-cell dysfunction seen in later stages. However, the last should be approached cautiously because hyperinflammatory side effects (due to a decrease in Tregs) are relatively common.…”
Section: Immunomodulation In Relation To Sars-cov-2mentioning
confidence: 99%
“…Previously, dual p110δ/γ inhibition with the pharmaceutical IPI-145 has been shown to be ineffective in combination with anti-PD-L1 therapy in murine MOC2 HNSCC [ 26 ]. However, it has also been shown that dual inhibition of p110δ/γ abrogates CD8+ T-cell function while selective inhibition of p110δ or p110γ does not [ 19 ]. Therefore, because our findings indicate PI3K p110γ inhibition alone enhances CD8 + T-cell recruitment and preserves CD8 + T-cell function, this provides a rationale to combine PI3K p110γ inhibition with PD-L1 checkpoint inhibitors against poorly immunogenic HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies indicate that inhibition of PI3K p110γ in combination with other therapies could enhance anti-tumor immune function. For example, a recent study in a murine melanoma model showed that adoptively transferred CD8+ T-cells treated with IPI-549 exhibit increased cytotoxicity [ 19 ]. Further, IPI-549, in conjunction with anti-PD1 therapy, led to a stronger anti-tumor effect than either therapy alone in mouse models of HNSCC, lung, and breast carcinoma [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation